Efekt kraju we wskaźnikach finansowych przedsiębiorstw na podstawie analizy skupień sektorów gospodarczych w wybranych krajach Unii Europejskiej - Koralun-Bereźnicka, Julia (Country Effect in Financial Ratios of Enterprises in Selected European Union Countries Through Cluster Analysis, 2009)
The main aim of the research is to identify the country effect as a factor influencing financial ratios of enterprises across selected EU countries. It is performed through a comparative cluster analysis based on enterprise performance within countries. The analysis involves 37 financial ratios calculated for each of the 13 sectors in 9 EU countries. The data was obtained from harmonized aggregated financial statements published by the European Commission in the BACH database. The methodology of the research involves multivariate statistical methods, including cluster analysis and multidimensional scaling. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 256-264